A Study of Social Self-Efficacy and Alexithymia Among Adolescents - Kavita Sharma (PT Inovasi Pratama Internasional, 2024)
This study explores the factors influencing social self-efficacy and alexithymia among adolescents, with a focus on gender, educational level, and sibling composition. A sample of 234 adolescents was analysed using descriptive statistics, independent t-tests, one-way ANOVA, and Pearson correlation analyses. The results indicate no significant gender differences in social self-efficacy and alexithymia. However, significant differences were observed across educational levels, with college students exhibiting higher social self-efficacy and lower alexithymia compared to younger students. Additionally, adolescents with siblings demonstrated higher social self-efficacy and lower alexithymia than only children. The study also found significant negative correlations between social self-efficacy and the subscales of alexithymia (Difficulty Identifying Feelings, Difficulty Describing Feelings, and Externally-Oriented Thinking), suggesting that higher social self-efficacy is associated with better emotional awareness and expression. These findings highlight the importance of tailored interventions that address both social and emotional skills, particularly for younger adolescents and only children.